2008
DOI: 10.1136/jnnp.2007.122119
|View full text |Cite
|
Sign up to set email alerts
|

Depersonalisation/derealisation symptoms and updating orientation in patients with vestibular disease

Abstract: Patients with peripheral vestibular disease have a deficit in the ability to update orientation on the environment and a high prevalence of DD symptoms, which may imply a high order effect of the vestibular impairment. Derealisation symptoms in vestibular disease may be a consequence of a sensory mismatch between disordered vestibular input and other sensory signals of orientation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
49
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 49 publications
(46 reference statements)
12
49
1
Order By: Relevance
“…There appears to be a complex, two-way interaction between vestibular function and affective state, which may be partly related to the contribution of the vestibular system to the control of autonomic function (e.g., heart rate, blood pressure, respiration) [50][51][52][53][54][55][56][57]. This kind of evidence suggests that vestibular impairment may cause a multitude of changes in cognition, emotion and personality, which is consistent with some evidence that vestibular disease is associated with unusually high rates of depersonalization/derealization symptoms, which include difficulty focussing attention and thoughts seeming blurred (e.g., [16,17]). …”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…There appears to be a complex, two-way interaction between vestibular function and affective state, which may be partly related to the contribution of the vestibular system to the control of autonomic function (e.g., heart rate, blood pressure, respiration) [50][51][52][53][54][55][56][57]. This kind of evidence suggests that vestibular impairment may cause a multitude of changes in cognition, emotion and personality, which is consistent with some evidence that vestibular disease is associated with unusually high rates of depersonalization/derealization symptoms, which include difficulty focussing attention and thoughts seeming blurred (e.g., [16,17]). …”
Section: Introductionsupporting
confidence: 70%
“…Since this study, many papers have been published documenting specific spatial memory and attention deficits in patients with different kinds of vestibular disorders ( [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]; see [25][26][27] for reviews). Given the severity of the symptoms in some vestibular disorders such as Meniere's disease, it is possible that cognitive dysfunction is an indirect consequence of symptoms such as vertigo.…”
Section: Introductionmentioning
confidence: 99%
“…This result seems to contrast with the greater occurrence of depersonalization-derealization symptoms in vestibular patients than healthy volunteers [64,65,67]. Jauregui-Renaud et al .…”
Section: Discussionmentioning
confidence: 99%
“…Birdane et al [21] have suggested that deficits in the sacculo-collic reflex, one of the subtypes of vestibular reflexes, may even serve as an early diagnostic marker of AD. Concidentally, many studies in both animals and humans over the last 2 decades, have shown that damage to the peripheral vestibular system causes deficits in memory and attention [26][27][28][29][30][31][32][33][34][35][36][37][38]. These cognitive impairments are thought to reflect the importance of the vestibular system in providing continuous information about self-motion to areas of the brain involved in spatial memory, such as the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Since AD is associated with vestibular dysfunction [21,22], and vestibular dysfunction is associated with cognitive impairment [26][27][28][29][30][31][32][33][34][35][36][37][38], the main aim of this experiment was to use the cognitive deficits caused by vestibular dysfunction to test a putative nootropic drug that has been investigated as a possible treatment for AD [16]. To this end, rats subjected to bilateral vestibular lesions were tested in the 5CSRTT, to determine whether the ampakine, CX717 [7,9], could have any beneficial effect.…”
Section: Introductionmentioning
confidence: 99%